Predictors of multi-domain cognitive decline following DBS for treatment of Parkinson's disease. (February 2022) - Rothlind, Johannes C.; York, Michele K.; Luo, Ping; Carlson, Kim; Marks, William J.; Weaver, Frances M.; Stern, Matthew; Follett, Kenneth A.; Duda, John E.; Reda, Domenic J.; ,; Follett, Kenneth; et al.
Abstract: Background: Statistically and clinically significant cognitive declines are observed in a small subset of individuals with Parkinson's Disease (PD) following treatment with Deep Brain Stimulation (DBS). Objectives: We examine the association between multi-domain cognitive decline (MCD) and demographic and baseline clinical variables and the incidence of serious adverse events (SAE) arising within a six-month interval following DBS for PD. Method: Study participants with PD who displayed MCD at 6-month follow-up evaluation after DBS (n = 18) were contrasted with individuals with PD from the same study who did not show cognitive decline after DBS (n = 146). Logistic regression analyses were employed to assess relationship between predictors, including age (>70 years old), pre-DBS cognitive screening test performance, SAE, and MCD. MCD+ and MCD-groups were also compared on other baseline clinical and demographic variables. Results: MCD showed modest association with older age and lower baseline neurocognitive screening performance, whereas the groups did not differ on most other baseline clinical and demographic variables. SAEs during the study interval were the most robust predictor of MCD in the DBS group. A variety of SAEs were documented in study participants experiencing MCD after DBS surgery, including, but not limited to, infections and small intracranial hemorrhages. Conclusions: Older age and lower baseline cognition measured prior to treatment are associated with MCD measured at six-months after DBS. SAE occurring following DBS surgery are also predictive of MCD. These predictors may reflect aspects of "frailty" in advanced PD. Risk factors for SAE warrant careful consideration in clinical trials. Highlights: Age shows modest associations with higher rate of cognitive decline after DBS for PD. Lower Baseline cognitive Functioning shows modest association with cognitive decline after DBS for PD. Serious Adverse Events are associated with Cognitive Decline after DBS for PD.